One last time a psychic medium speaks to those we have loved and lost - Edward, John (New York : Berkley Books, 1999)
The medium describes how he discovered and developed his psychic abilities, and shares his experiences communicating between his clients and their deceased loved ones
Originally published: New York: Berkley, 1998.
93619
Keywords: Edward, John; Mediums -- United States